The Chitranjan Ranawat Award: Running Subcuticular Closure Enables the Most Robust Perfusion After TKA: A Randomized Clinical Trial - Wyles, Cody C. (Clin Orthop Relat Res, 2015)
BACKGROUND: Maintaining robust perfusion is an important physiologic parameter in wound healing. The effect of different closure techniques on wound perfusion after total knee arthroplasty (TKA) has not been established previously and may have implications for wound healing. QUESTIONS/PURPOSES: We asked whether a running subcuticular, vertical mattress, or skin staple closure technique enables the most robust wound perfusion after TKA as measured by laser-assisted indocyanine green angiography (LA-ICGA) in patients without specific risk factors for wound healing complications. METHODS: Forty-five patients undergoing primary TKA without comorbidities known to impact wound healing and perfusion were prospectively randomized to receive superficial skin closure with one of the following techniques: (1) running subcuticular (3-0 monofilament); (2) vertical mattress (2-0 nylon); or (3) skin staples. Twenty procedures were performed by RTT, 15 by RJS, and 10 by FHS. All surgeons used an anterior skin incision over the medial third of the patella in combination with a median parapatellar arthrotomy. Perfusion was assessed with a LA-ICGA device and software system immediately after closure to quantify fluorescence. Twenty-seven points were assessed immediately after closure in the operating room in each patient (nine along the incision and nine pairs medial and lateral to the incision). Mean incision perfusion was determined from the nine points along the incision with higher values indicating greater blood flow. Mean perfusion impairment was determined by calculating the difference between the nine pairs of surrounding skin and the nine points along the incision with smaller values indicating less perfusion impairment. These parameters were compared with analysis of variance (ANOVA) and subsequent pairwise comparisons with an unadjusted analysis as well as a multivariate analysis that adjusted for age, sex, and body mass index. Patients were followed for a mean of 7 months after surgery (range, 3–12 months) for possible incision-related complications. No patents were lost to followup. RESULTS: Running subcuticular closure demonstrated the best overall perfusion. Mean incision perfusion in fluorescent units with SD was as follows: running subcuticular, 64 (16); vertical mattress, 32 (18); and staples, 19 (7) (ANOVA p < 0.001). The running subcuticular closure demonstrated the least impairment of perfusion among the closures compared. Mean perfusion impairment was as follows: running subcuticular, 21 (12); vertical mattress, 37 (24); and staples, 69 (27) (ANOVA p < 0.001). All Tukey-adjusted pairwise comparisons from both metrics likewise favored the subcuticular closure (p < 0.001) both before and after adjusting for age, sex, and body mass index. One patient in the vertical mattress cohort experienced a surgical site infection; no other wound-related complications were observed in this study. CONCLUSIONS: The method of closure can influence skin and soft tissue perfusion after TKA. Running subcuticular closure enables the most physiologic robust blood flow, which may improve wound healing. However, the clinical importance of these findings remains uncertain, because patients in this study were selected because they lacked risk factors for wound healing complications. Studies with this modality in specific patient populations at higher risk for wound complications will be necessary to quantify the clinical advantage of using running subcuticular closure. LEVEL OF EVIDENCE: Level I, therapeutic study.